Synthesis and Characterization of Nano Activated Carbon Tea Waste (Camellia sinensis L.) Viewed from the Content and Ratio of Orthophosphoric Acid - Wijaya, Daniel Ricky Putra; Martono, Yohanes; Riyanto, Cucun Alep (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2018)
Waste of tea is still limited in terms of utilization, potentially to be made into nanocarbon. In this research, nanocarbon synthesis from the waste of tea through carbonation method using furnace and purification with HNO3 with activator substance used is H3PO4. The specific objective of this study was to determine the optimal levels and ratios of ortho-phosphoric acid and to determine the properties and characteristics of nanocarbon from tea waste. Based on the FT-IR spectra, the best ortho-phosphate acid levels and ratios are 50% and 1:2 (w/w) H3PO4. The XRD analysis showed that the activated carbon dregs obtained were C graphite which was characterized by the diffraction peak at 2theta: 26.2°; 26.5°; 42.2°; 42.4°; and 44.3°. Based on the TEM image obtained shows that the activated carbon of the resulting tea waste has a particle size of 20-40 nm.